Assessment of Transvaginal Ultrasound Cervical Length Image Quality. Issue 3 (March 2017) - Boelig, Rupsa C.; Feltovich, Helen; Spitz, Jean Lea; Toland, Gregory; Berghella, Vincenzo; Iams, Jay D.
Abstract : OBJECTIVE: To use data from the Cervical Length Education and Review program to evaluate the quality of transvaginal cervical length ultrasonography by trained imagers (ie, ultrasonographers, radiologists, perinatologists). METHODS: This is a retrospective observational study of data from the Cervical Length Education and Review program. Candidates underwent an online lecture series, examination, and submitted a batch of images for review. For a candidate's batch of images to pass, all images must meet at least seven of the nine criteria assessed, the overall batch score needs to be 80% or greater, correct caliper placement must be met for all images, and the same criterion cannot be consistently missed. We also examined a subset of these criteria-appropriate image acquisitions, defined as an image that demonstrated both internal and external os and visualization of the entire endocervical canal. Primary outcome was the overall initial candidate pass rate; secondary outcomes included distribution of criteria missed in images and percentage of images that was inadequately acquired. RESULTS: Six hundred eighty-seven candidates submitted 3, 748 images between June 10, 2012, and August 18, 2016. Eighty-five percent of candidates were ultrasonographers. Of the 687 initial batches submitted, 105 (15%) did not pass. Eight hundred thirty-seven images (22%) of all images failed at least one criterion; the most common image deficiencies were in "anterior width of cervix equals the posterior width" (33%), "failure to visualize" the internal or external os (29%), "cervix occupies 75% of image and bladder area visible" (33%), and incorrect caliper placement (24%). Two hundred fifty-six (7%) of all images failed to meet our criteria for adequate image acquisition. CONCLUSION: Fifteen percent of trained imagers failed to obtain appropriate cervical length imaging. This highlights the importance of a standardized cervical length training and certification program. Abstract : Among trained imagers undergoing structured training for transvaginal cervical length measurement, 15% fail to meet standards, highlighting the importance of standardized training and certification.